Dipyridylphenylamine-based chemodosimeter for sulfite with optimizing ratiometric signals via synchronous fluorescence spectroscopy. (January 2017) - Wu, Jianwei; Qu, Yi; Wang, Linlin; Huang, Liliang; Rui, Yichuan; Cao, Jian; Xu, Jingli
Abstract: A dipyridyltriphenylamine derivative, ( E )-4-(2-nitrovinyl)- N, N -bis(4-(pyridin-4-yl)-phenyl)aniline, was synthesized as a fluorescent probe for sulfite ion, which can be used in detecting excessive addition of sulfite in the food industry. The chemodosimeter can output far-red to near-infrared emission under both aqueous and solid state conditions exhibiting potential applications in the field of luminescent functional materials. Based on synchronous fluorescence spectroscopy, a ratiometric method was developed for determination of sulfite ion with small overlap in the emission spectrum, whose emission band is narrower than that observed in normal emission spectrum. Graphical abstract: A dipyridyltriphenylamine derivative, ( E )-4-(2-nitrovinyl)- N, N -bis(4-(pyridin-4-yl)- phenyl)aniline, was synthesized as a fluorescent probe for detecting sulfite anion. Combining with synchronous fluorescence spectroscopy technology and intramolecular charge transfer molecule, the molecular probe showed narrow full width at half-maximum and minimum overlap of emission spectra across the sensing process. Highlights: A fluorescent dye (DPTPA2) was synthesized with near-infrared emission. Synchronous Fluorescence Spectroscopy was introduced into the molecular probe platform. DPTPA2 showed narrow full width at half-maximum and minimum overlap of emission spectra. The new dye was shown to be a selective probe for sulphite ion.